Triangle Inequality/Real Numbers

From ProofWiki
Jump to navigation Jump to search

Theorem

Let $x, y \in \R$ be real numbers.

Let $\size x$ denote the absolute value of $x$.


Then:

$\size {x + y} \le \size x + \size y$


Proof 1

\(\displaystyle \size {x + y}^2\) \(=\) \(\displaystyle \paren {x + y}^2\)
\(\displaystyle \) \(=\) \(\displaystyle x^2 + 2 x y + y^2\)
\(\displaystyle \) \(=\) \(\displaystyle \size x^2 + 2 x y + \size y^2\)
\(\displaystyle \) \(\le\) \(\displaystyle \size x^2 + 2 \size {x y} + \size y^2\) Negative of Absolute Value‎
\(\displaystyle \) \(=\) \(\displaystyle \size x^2 + 2 \size x \cdot \size y + \size y^2\) Absolute Value Function is Completely Multiplicative
\(\displaystyle \) \(=\) \(\displaystyle \paren {\size x + \size y}^2\)


Then by Order is Preserved on Positive Reals by Squaring:

$\size {x + y} \le \size x + y$

$\blacksquare$


Proof 2

This can be seen to be a special case of Minkowski's Inequality, with $n = 1$.

$\blacksquare$


Proof 3

We have that Real Numbers form Ordered Integral Domain.

Therefore Sum of Absolute Values on Ordered Integral Domain applies directly.

$\blacksquare$


Proof 4

We do a case analysis.


$(1): \quad x \ge 0, y \ge 0$

\(\displaystyle x\) \(\ge\) \(\displaystyle 0\)
\(\displaystyle y\) \(\ge\) \(\displaystyle 0\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle \size {x + y}\) \(=\) \(\displaystyle x + y\)
\(\displaystyle \) \(=\) \(\displaystyle \size x + \size y\)

$\Box$


$(2): \quad x \le 0, y \le 0$

\(\displaystyle x\) \(\le\) \(\displaystyle 0\)
\(\displaystyle y\) \(\le\) \(\displaystyle 0\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle \size {x + y}\) \(=\) \(\displaystyle -x - y\)
\(\displaystyle \) \(=\) \(\displaystyle \size x + \size y\)

$\Box$


$(3): \quad x \ge 0, y \le 0$

We have that $\size x = x$ and $\size y = -y$.

In this case we show:

$\size {x + y} \le \max \set {\size x, \size y}$


Let $\size x \le \size y$.

Then:

\(\displaystyle x\) \(\le\) \(\displaystyle -y\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle y\) \(\le\) \(\displaystyle y + x\) as $x \ge 0$
\(\displaystyle \) \(\le\) \(\displaystyle 0\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle \size {x + y}\) \(=\) \(\displaystyle -\paren {x + y}\)
\(\displaystyle \) \(\le\) \(\displaystyle -y\)
\(\displaystyle \) \(=\) \(\displaystyle \size y\)


Let $\size x \ge \size y$.

Then:

\(\displaystyle x\) \(\ge\) \(\displaystyle -y\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle x\) \(\ge\) \(\displaystyle x + y\) as $y \le 0$
\(\displaystyle \) \(\ge\) \(\displaystyle 0\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle \size {x + y} =\) \(=\) \(\displaystyle x + y\)
\(\displaystyle \) \(\le\) \(\displaystyle x\)
\(\displaystyle \) \(=\) \(\displaystyle \size x\)


We have $\max \set {a, b} \le a + b$ for positive real numbers $a$ and $b$.

The result follows by taking $a = \size x$ and $b = \size y$.

$\Box$


$(4): \quad x \le 0, y \ge 0$

Follows by symmetry from the case $(3)$.

$\blacksquare$


Examples

Example: $\size {-1 + 3}$

$2 = \size {-1 + 3} \le \size {-1} + \size 3 = 1 + 3 = 4$


Sources